Power Moves in Politics: How Eddy Soeparno Conquered the 2024 Legislative Election in West Java III - Syafitri, Virnie (Jurnal Inovasi Global, 2025)
This study examines the political campaign strategies employed by Eddy Soeparno in the 2024 legislative election. The West Java III electoral district competes for 9 seats. West Java III includes the city of Bogor and the Cianjur Regency. The research adopts a qualitative approach with a case study design and utilizes Peter Schroder's political strategy theory as the conceptual framework to analyse Eddy Soeparno’s strategy, focusing on his use of both offensive and defensive strategies. The findings reveal that Soeparno's campaign was marked by a strong emphasis on emotional communication, issue segmentation, resource mobilization, reputation building, and strategic continuity. By focusing on tangible, long-term programs such as bore wells, solar-powered street lighting, and public facility revitalization, he successfully fostered trust and loyalty among voters. His ability to tailor campaign messages to address specific local issues, such as water scarcity in Cianjur and traffic congestion in Bogor, further enhanced his appeal. Additionally, Soeparno’s commitment to maintaining volunteer networks and ensuring the continuation of social programs after the election demonstrated his dedication to long-term engagement. The study underscores the importance of emotional bonding and issue-specific strategies in modern political campaigns and highlights the integration of offensive and defensive tactics as crucial for electoral success. The findings suggest that political candidates should prioritize emotional connection with constituents, tailor campaigns to local contexts, sustain post-election engagement, and balance both offensive and defensive strategies for a more effective and lasting impact on voters.